2023
DOI: 10.1155/2023/3251211
|View full text |Cite
|
Sign up to set email alerts
|

Galangin-Loaded Gold Nanoparticles: Molecular Mechanisms of Antiangiogenesis Properties in Breast Cancer

Abstract: Angiogenesis is important for tissue during normal physiological processes as well as in a number of diseases, including cancer. Drug resistance is one of the largest difficulties to antiangiogenesis therapy. Due to their lower cytotoxicity and stronger pharmacological advantage, phytochemical anticancer medications have a number of advantages over chemical chemotherapeutic drugs. In the current study, the effectiveness of AuNPs, AuNPs-GAL, and free galangin as an antiangiogenesis agent was evaluated. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 45 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…8). The results of the current study agree with the finding of several studies (Alhadrami et al, 2021;Qaddoori & Al-Shmgani, 2023).…”
Section: -Ultraviolet-visible Spectroscopysupporting
confidence: 93%
“…8). The results of the current study agree with the finding of several studies (Alhadrami et al, 2021;Qaddoori & Al-Shmgani, 2023).…”
Section: -Ultraviolet-visible Spectroscopysupporting
confidence: 93%
“…Galangin is the main functional component extracted from Alpinia officinarum Hance [11,12]. Many studies have shown that galangin can inhibit the growth and invasion of various malignant tumors, including lung cancer [13], breast cancer [14], liver cancer [15], bladder cancer [16], and leukemia [17]. Its anticancer spectrum is relatively wide and has a good application prospect.…”
Section: Discussionmentioning
confidence: 99%
“…AgNO3 solution was prepared by dissolving 0.0618 g of AgNO3 in 100 ml of distilled water at 45 °C to obtain a 1 mM silver nitrate solution, then 2 ml of (1%) trisodium citrate was added. The solution was kept on a stirrer for minutes, and then stored until used at 4°C [8]. Freshly prepared bromelain with a final concentration of 10 mg/mL dissolved in distilled water was added to the AgNPs solution and stirred for 6 hours [9].…”
Section: Preparation Of Bromelain and Agno3 Solutionsmentioning
confidence: 99%